2016
DOI: 10.1108/cg-08-2015-0110
|View full text |Cite
|
Sign up to set email alerts
|

Earnings quality and audit attributes in high concentrated ownership market

Abstract: Purpose The purpose of this study is to examine the effect of the audit committee (AC) independence, financial expertise, internal audit function, audit quality and ownership concentration on earnings quality (EQ) and, consequently, ascertain whether the AC’s independence and financial expertise has a moderating effect on the relationship between internal audit function and EQ. Design/methodology/approach The study sample is 508 firms listed on the Main Market of Bursa Malaysia (formerly known as Kuala Lumpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 113 publications
6
62
0
Order By: Relevance
“…It is also found that LEV is positively and significantly related to ABSDA1 and ABSDA2. This positively significant result is consistent with previous studies (Al-Rassas & Kamardin, 2016;Saleh et al, 2005Saleh et al, , 2007Salleh & Haat, 2013;Salleh et al, 2012). This is because companies that face financial difficulties attempt to report higher returns in order to hide their financial constraints (Campa, 2015;Park & Shin, 2004).…”
Section: Regression Modelssupporting
confidence: 90%
“…It is also found that LEV is positively and significantly related to ABSDA1 and ABSDA2. This positively significant result is consistent with previous studies (Al-Rassas & Kamardin, 2016;Saleh et al, 2005Saleh et al, , 2007Salleh & Haat, 2013;Salleh et al, 2012). This is because companies that face financial difficulties attempt to report higher returns in order to hide their financial constraints (Campa, 2015;Park & Shin, 2004).…”
Section: Regression Modelssupporting
confidence: 90%
“…From the perspective of agency theory, independence and expertise of audit committee directors are much significant in maintaining the integrity of financial reporting and increase the monitoring quality as they are representatives of the shareholders and minority in particular (Watts & Zimmerman, 1978;Fama & Jensen, 1983).Independent directors have more motivation and expertise to reduce opportunistic behaviour, fraud and misleads in the accounting statements and in which to guarantee the interests of shareholders (Watts & Zimmerman, 1978;Baatwah et al, 2015a), and the quality of financial information (Al-Rassas & Kamardin, 2016). Moreover, directors with financial expertise in audit committee are more efficient when they are independent (Sharma & Kuang, 2014).…”
Section: Audit Committee Independencementioning
confidence: 99%
“…It is claimed that large board size has directors with diverse expertise may strengthen internal controls and capability of directors to monitor the actions of firm's management. Hence, reduce the late issuance of audit report (Basuony et al, 2016); Big4 audit firm (BIG4) is a dummy variable equal "1" if the firm was audited by one of the Big4 auditors and "0" otherwise (Al-Rassas & Kamardin, 2016;Ghafran &Yasmin, 2018). The recognized BIG4 audit firms have advanced resources, better technology and high expertise to provide the audit task by high quality and in faster time compared to non-Big4 firms (Alkhatib & Marji, 2012) and hence, they will provide audit report in a shorter time (Basuony et al, 2016).…”
Section: Variables Measurementsmentioning
confidence: 99%
“…Consequently, previous studies have extensively examined the influence of BOD mechanisms, i.e., CEO chairmanship (Abdul-Rahman & Ali, 2006; chairman independence (Al-Zyoud, 2012;Habbash, 2011;Mohammad et al, 2016), board independence (Chandren, Ahmad, & Ali, 2015;Ku Ismail & Abdullah, 2013;Mansor, Che-Ahmad, Ahmad-Zaluki, & Osman, 2013), board size (Abdullah & Ku Ismail, 2016;Mohammad et al, 2016;Zalata, Tauringana, & Tingbani, 2018), board meetings (Ahmed, 2017;Mansor et al, 2013;Mohammad et al, 2016), women on the boards (Abdullah & Ku Ismail, 2012Buniamin et al, 2012;Ku Ismail & Abdullah, 2013), board directors with corporate background and experience (Ahmed, 2017;Buniamin et al, 2012;Xie, Davidson, & DaDalt, 2003) and board directors with multiple directorships (Baccouche & Omri, 2014;Chandren et al, 2015;Jamaludin, Sanusi, & Kamaluddin, 2015) on mitigating the level of EM. Further, other studies also have extensively examined the influence of AC mechanisms, i.e., AC size (Abdullah & Ku Ismail, 2016;Al-Rassas & Kamardin, 2015;Mansor et al, 2013), AC meeting (Abdul-Rahman & Ali, 2006;Al-Rassas & Kamardin, 2015;Ishak, Haron, Salleh, & Rashid, 2011), AC independence (Abdul-Rahman & Ali, 2006;Al-Rassas & Kamardin, 2016;Haji-Abdullah & Wan-Hussin, 2015), women in the AC (Ku Ismail & Abdullah, 2013;Salleh & Haat, 2013), AC accounting expertise …”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the majority of firms have implemented the MCCG, ACs have not been effective in constraining EM (Chandrasegaram, Rahimansa, Rahman, Abdullah, & Mat, 2013). Thus, more studies are recommended (Al-Rassas & Kamardin, 2016;Chandrasegaram et al, 2013;Inaam & Khamoussi, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%